THE IMPLEMENTATION OF REFORESTATION CLEAN DEVELOPMENT MECHANISM IN BROMO TNEGGER SEMERU NATIONAL PARK - Wardani, Novita Kusuma (FIA UB, 2013)
Abstract: The Implementation of Reforestation Clean Development Mechanism in Bromo Tnegger Semeru National Park. This research used to a qualitative method. Data are collected through field work and used multiple sources of evidence, namely, documentations, archival records, direct and participant observation, and open-ended interviews with relevant respondents from the parties involving in the project. This study focuses on the role of policy content and actors in the implementation and the social, economic and political condition which affect the implementation. The results show that while the implementation of A/R CDM in BTSNP especially In field work (planting and maintenance) relative success, the administration of the project still face some problems. During three years of its implementation 310 ha areas have been planted. The A/R CDM plantation can be well implemented because of the content of the policy, the involved actors as well as support of social, economic and political condition. Innovative policy and the strategy which use to implement it resulted in the high degree of plantation survival rate. Keyword: Analyze the CDM Policy, implementation, innovative Abstrak: Implementasi Pelaksanaan Mekanisme Pembangunan Bersih Reboisasi di Taman Nasional Bromo Tengger Semeru. Penelitian ini menggunakan metode kualitatif. Data dikumpulkan melalui studi lapangan dan menggunakan beberapa sumber bukti, yaitu, dokumentasi, catatan arsip, observasi dan partisipasi langsung, dan wawancara terbuka dengan responden yang relevan. Penelitian ini memfokuskan pada peran konten kebijakan dan aktor dalam pelaksanaan dan kondisi sosial, ekonomi dan politik yang mempengaruhi pelaksanaannya. Hasil menunjukkan bahwa disaat pelaksanaan A/R CDM di BTSNP terutama dalam kerja lapangan (penanaman dan pemeliharaan) relatif sukses, administrasi proyeknya masih menghadapi beberapa masalah. Selama tiga tahun pelaksanaannya sudah 310 ha daerah yang telah ditanami. Perkebunan A/R CDM dapat dilaksanakan dengan baik karena isi dari kebijakan tersebut, aktor yang terlibat serta dukungan kondisi sosial, ekonomi dan politik. Kebijakan yang inovatif dan strategi yang digunakan untuk menerapkannya menghasilkan tingkat yang tinggi dalam kelangsungan hidup tanaman. Kata Kunci: Analisis Kebijakan CDM, pelaksanaan, dan inovatif